Pharmacological characterization of hetrombopag, a novel orally active human thrombopoietin receptor agonist. Issue 11 (29th August 2018) - Xie, Chengying; Zhao, Huajun; Bao, Xubin; Fu, Haoyu; Lou, Liguang
Abstract: Nonpeptide thrombopoietin receptor (TPOR/MPL) agonists, such as eltrombopag, have been used to treat thrombocytopenia of various aetiologies. Here, we investigated the pharmacological properties of hetrombopag, a new orally active small‐molecule TPOR agonist, in preclinical models. Hetrombopag specifically stimulated proliferation and/or differentiation of human TPOR‐expressing cells, including 32D‐MPL and human hematopoietic stem cells, with low nanomolar EC50 values through stimulation of STAT, PI3K and ERK signalling pathways. Notably, hetrombopag effectively up‐regulated G1 ‐phase–related proteins, including p‐RB, Cyclin D1 and CDK4/6, normalized progression of the cell cycle, and prevented apoptosis by modulating BCL‐XL/BAK expression in 32D‐MPL cells. Moreover, hetrombopag and TPO acted additively in stimulating TPOR‐dependent signalling, promoting cell viability, and preventing apoptosis. Orally administered hetrombopag specifically promoted the viability and growth of 32D‐MPL cells in hollow fibres implanted into nude mice with much higher potency than that of the well‐known TPOR agonist, eltrombopag, in association with activation of TPOR‐dependent signal transduction in vivo. Taken together, our findings indicate that, given its favourable pharmacological characteristics, hetrombopag may represent a new, orally active, small‐molecule TPOR agonist for patients with thrombocytopenia.